The Reasons Of Families Abstention From Attending Foot Ball Stadiums And Its Relationship With Social Values A Case Study Of El Zayania City – Chevalley - Louakhch Ataellah .,; Cherfi Ameur ., (sports creativity, 2025)
The present paper deals with the reasons of families abstention from attending the football stadiums, and its relationship with social values, according to various theoretical backgrounds. The study gets a lot of results indicating that the social values system has a direct impact on limiting these obstacles. To achieve the goals, we have prepared a survey addressed to a group of Algerian families in the city of El Zayania, Chevalley. The number of families has been estimated at 280, representing 59 % of the whole population study. The present research is descriptive and connected to two variables in a way to identify the causes and their relationship with social values. On the other side, it defines differences between social values indexes to explain the reality of the relationship between families abstention from attending football stadiums and social values that exceed the sports activity practice to include social and psychological characteristics of the individual.